Formulation parameters effects on the performances of concrete equivalent mortars incorporating different ratios of recycled sand. (May 2020) - Ghorbel, Elhem; Wardeh, George; Gomart, Hector; Matar, Pierre
The present research investigates the feasibility of manufacturing masonry mortars with recycled sand. The primary aim is to study the effect of fine recycled aggregates on fresh and hardened states with properties. Two series of mortars were designed by substituting natural sand with recycled sand, with variable sand replacement ratios ranging from 0% to 100%. One series, named variable workability series, has variable workability with constant water to cement ratio ( W/C ), while the other series, called constant workability series, has a constant workability with variable W/C . The density, air content, and slump of mortars in fresh state were measured with a special attention devoted to the effect of pre-saturation of recycled sand on the slump. In the hardened state, the microstructure was studied by means of water accessible porosity test and mercury intrusion porosimetry test. Flexural and compressive strength as well as the dynamic modulus of elasticity were also examined and the correlations between these properties and the microstructure have been established. It was found that the properties of mortars with recycled sand are lower than those obtained for the natural sand mortar (−20% for variable workability series and −45% for constant workability series at the age of 28 days). For the series with variable workability, mechanical properties decrease to a step starting from 30% replacement ratio, while linearly decrease for the mortars with constant workability. The difference between the two series lies in the difference in total porosities and the pore size distribution.